Knowledge and practice regarding contact lens wear and care among undergraduate students in Universiti Sains Malaysia - Khairi, Nurul Akmal Asnil (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Contact lenses are thin optical correction lenses worn on the eye and rest on the cornea’s surface. Contact lens requires knowledge and practice regarding contact lens wear and care to control its progression and its complication effectively. Objective of this study aims to determine the knowledge and practice regarding contact lens wear and care and factor associated with the practice of contact lens wear and care among undergraduate students in Universiti Sains Malaysia. A cross-sectional study design was used in this research. The questionnaire was collected by using online method. The questionnaire using Google Form was sent through WhatsApp. Descriptive statistics were used to describe the respondent and identify the level of knowledge and practice of contact lens wear and care among undergraduate students in Universiti Sains Malaysia. Pearson Chisquare were used to test the association between variables. Majority of respondents were having poor knowledge and practice of contact lens wear and care. The result revealed that there was no association between knowledge and practice of contact lens wear and care as p-value > 0.05. The results of this study have shown an unsatisfactory level of knowledge among undergraduate students indicated by poor knowledge level and poor practices related to contact lens wear, care, and complications. There is a need for more education, awareness, and behavioural program to contact lens wearers especially undergraduate students regarding contact lens usage, care, and its related complications, which should be provided by all primary eye care practitioners